APLIKASI PUPUK ORGANIK CAIR Gracilaria gigas, CANGKANG TELUR DAN KULIT PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI SAWI CAISIM (Brassica juncea L.) - Vivin Andriani (Teknosains, 2020)
The aim of this study was to determine the effect of Gracilaria gigas raw liquid organic fertilizer, eggshell and banana peel on the growth and production of mustard caisim plants and to find out the most optimal concentration on the growth and production of mustard greens .. Liquid organic fertilizer made with the composition of Gracilaria gigas 2.5 kg, egg shell 1 kg, banana peel 2.5 kg, water 8 liters, sugar 2 kg and EM4 1 liter. This study used four treatments with a concentration of each treatment that is 0% as control, 5%, 10%, 15%, 20%, for 30 days after the cabbage plant is treated. The design used in this study was a Completely Randomized Design consisting of 4 treatments with 6 replications. The results showed that administration of liquid organic fertilizer from Gracilaria gigas, eggshells and banana peels had a significant effect (p <0.05) on plant height, number of leaves, and wet weight of mustard greens. The conclusion generated in this study is the use of liquid organic fertilizer from Gracilaria gigas, egg shells and banana peel with a concentration of 10% can increase the growth and production of cabbage caisim plants well.